(untitled) (Research, Society and Development, 2021)
Introduction: The preparation for surgery begins with the preoperative period, the time of hospitalization is a particularly uncomfortable situation for children and caregivers due to exposure to a new environment and painful procedures. Objective: The study identified and analyzed through free evocations the social representation and the feelings mentioned by companions of children in preoperative situation, in a university hospital in Rio de Janeiro. Method: This is a qualitative study based on theory of social representations in it approach. Thus, for the research, data were collected from 71 family caregivers through the technique of free evocations of words. Results: According to the results it was possible to observe that fear is a term that has the central position in relation to the others, thus providing a solar graphic configuration. Conclusion: At the end of the study it was possible to observe that the free evocations were divided into three dimensions: a strong negative effective dimension; another discrete positive affective dimension; and finally a biomedical demension with median representation.